2023
DOI: 10.1002/alz.13480
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous treatment effects of metformin on risk of dementia in patients with type 2 diabetes: A longitudinal observational study

Huilin Tang,
Jingchuan Guo,
C. Elizabeth Shaaban
et al.

Abstract: INTRODUCTIONLittle is known about the heterogeneous treatment effects of metformin on dementia risk in people with type 2 diabetes (T2D).METHODSParticipants (≥ 50 years) with T2D and normal cognition at baseline were identified from the National Alzheimer's Coordinating Center database (2005–2021). We applied a doubly robust learning approach to estimate risk differences (RD) with a 95% confidence interval (CI) for dementia risk between metformin use and no use in the overall population and subgroups identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…100 However, current evidence on the attenuated risk of dementia with metformin use remains inconclusive. 101,102 Although some studies suggested that metformin might reduce the risk of dementia and improve cognition in patients with diabetes, the results were limited by small sample sizes and inadequate adjustment for confounding factors. On the other hand, some researchers reported an increased risk of dementia with metformin.…”
Section: Dementia and Cognitive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…100 However, current evidence on the attenuated risk of dementia with metformin use remains inconclusive. 101,102 Although some studies suggested that metformin might reduce the risk of dementia and improve cognition in patients with diabetes, the results were limited by small sample sizes and inadequate adjustment for confounding factors. On the other hand, some researchers reported an increased risk of dementia with metformin.…”
Section: Dementia and Cognitive Dysfunctionmentioning
confidence: 99%
“…This might lead to subclinical deficiency, which contributes to cognitive decline. 104,105 Although the effects of metformin on cognitive function might depend on the dose and treatment duration, 102 there are limited interventional studies investigating the effects of metformin and its relationships with vitamin B12 on cognitive function. 52…”
Section: Dementia and Cognitive Dysfunctionmentioning
confidence: 99%